1997
DOI: 10.1093/emboj/16.3.495
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression in the liver of truncated Met blocks apoptosis and permits immortalization of hepatocytes

Abstract: Hepatocyte growth factor induces proliferation, motility and differentiation of epithelial cells through the tyrosine kinase receptor encoded by the MET proto‐oncogene. The cytoplasmic portion of Met (referred to as cyto‐Met) is activated but only weakly transforming. In order to determine the effect of activated Met on hepatocytes, we have targeted truncated Met expression to the liver by incorporating the cDNA into a vector carrying the entire human a‐1‐antitrypsin transcriptional unit. Transgenic expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 60 publications
(62 reference statements)
4
124
2
Order By: Relevance
“…We succeeded in establishing permanent cell lines which stably expressed HBx by isolating hepatocytes from HBx/p53-null and HBx/AT-cyto-MET bitransgenic animals. Importantly, HBx was able to overcome the known resistance to apoptotic death conferred to cells by p53 de®ciency, or by association of activated c-Met with the anti-apoptotic protein BAG-1 (Amicone et al, 1997;Bardelli et al, 1996;Hooper, 1994). The observation that HBx-expressing cells were equally sensitive to apoptotic signals provided by a DNAdamaging agent and by oxidative stress may be relevant to hepadnavirus pathogenesis, as recent studies have shown that the oxidative burst associated with viral infections leads to DNA damage through increased production of toxic oxygen radicals (Peterhans, 1997;Petersen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We succeeded in establishing permanent cell lines which stably expressed HBx by isolating hepatocytes from HBx/p53-null and HBx/AT-cyto-MET bitransgenic animals. Importantly, HBx was able to overcome the known resistance to apoptotic death conferred to cells by p53 de®ciency, or by association of activated c-Met with the anti-apoptotic protein BAG-1 (Amicone et al, 1997;Bardelli et al, 1996;Hooper, 1994). The observation that HBx-expressing cells were equally sensitive to apoptotic signals provided by a DNAdamaging agent and by oxidative stress may be relevant to hepadnavirus pathogenesis, as recent studies have shown that the oxidative burst associated with viral infections leads to DNA damage through increased production of toxic oxygen radicals (Peterhans, 1997;Petersen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Primary hepatocytes were isolated from p53-null and HBx/p53-null mice, giving rise to spontaneously immortalized cells called MHP53N and MHXP53N, which failed to grow in soft agar and retained an hepatocyte-like morphology (TP, manuscript in preparation). In parallel, we studied two other hepatocyte cell lines: MMHD3, established from a ATcyto-MET transgenic mouse, which express a truncated form of c-Met and are known to be resistant to di erent apoptotic stimuli (Amicone et al, 1997) and X-Met cells derived from the liver or a HBx/AT-cyto-MET bitransgenic animal (MT, unpublished data). Both these cell lines display a phenotype of well di erentiated hepatocytes, and they produce high levels of p53 mRNA as shown by Northern blot analysis ( Figure 3).…”
Section: Hbx Expression Sensitizes Immortalized Hepatocytes To DI Erementioning
confidence: 99%
See 1 more Smart Citation
“…For example, SF was found to protect Madin-Darby canine kidney (MDCK) renal tubular epithelial cells against apoptosis induced by detachment of cells from their substrate (Frisch and Francis, 1994); and infusion of SF after mitogenic activation of liver ductal epithelium by the hepatocarcinogen 2-acetylamino¯uorene stimulated motility and inhibited apoptosis of ductal and periductal cells (Nagy et al, 1996). Over-expression of the antiapoptotic protein Bag-1 in MLP-29 liver progenitor cells enhanced the ability of SF to inhibit apoptosis induced by protein kinase inhibitor staurosporine, although the mechanism is unclear (Bardelli et al, 1996); and Tpr-Met, a constitutively active oncogenic form of c-Met, also enhanced protection against staurosporine (Amicone et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…An infusion of HGF inhibited apoptosis of rat hepatic ductal cells after the administration of the hepatocarcinogen 2-acetylaminofluorene (Nagy et al, 1996). Furthermore, transgenic expression in the liver of truncated Met, a constitutively active oncogenic form of c-met, blocked staurosporine-induced apoptosis of hepatocytes (Amicine et al, 1997).…”
mentioning
confidence: 97%